The Symbolism and Aesthetics of the Window as a Visual Motif in the TV Series “The Handmaid’s Tale” - Ángeles Martínez-García; Mónica Barrientos-Bueno (Series. International journal of tv serial narratives)
Despite the fact that the TV series "The Handmaid’s Tale" has been widely researched, most studies have addressed aspects like narrative, feminism, violence against women or visual and compositional elements, such as the use of light and the symbolism of colour. However, there is still a dearth of scholarly works focusing on the analysis of the series’ staging and art direction. Accordingly, a comprehensive enquiry is performed here into one such aspect, namely, the windows appearing in the first season of the series. The aim is to verify the aesthetic and staging resources used when windows appear on screen. Additionally, the intention is to determine the kind of windows that stand out because of their symbolism and which are also in keeping with the core concept of the first season of the series. A specially designed analytical tool is employed to examine three of the most relevant windows – those of June/Offred’s bedroom, Commander Fred’s study and Serena’s bedroom – arriving at the conclusion that they are interwoven in both the plot and the characters at a narrative and symbolic level.